EFFECT OF SOIL PH ON THE APPEARANCES OF ARBUSCULAR MYCORRHIZAL FUNGI : - Jungjai , Orathai; Bodeerat, Supattra Charoenpakdee (PSRU Journal of Science and Technology, 2021)
The objective of this research is to study the effect of soil pH on the appearances of arbuscular mycorrhizal fungi (AMF) using sorghum (Sorghum bicolor (L.) Moench.) as the host plant. Thirty soil samples were collected in Phitsanulok and Sukhothai Provinces. All soil samplings were mixed, lower soil pH using chicken dung and higher soil pH using limestone. Soil was divided into 3 treatments including acid soil (pH 4-5) neutral soil (pH 6.5-7.5) and basic soil (pH 9-10). Each treatment had 5 replications and each replication had 5 sorghum seedlings per pot. All sorghums were cultured in greenhouse and watering with groundwater for 12 weeks. Growth of sorghum, height, fresh and dry of shoot weight, fresh and dry of root weight, number of AMF spore by wet sieving and species identification by spore morphology were recorded. It was found that all AMF obtained belong to genus Acaulospora (7 morphotaxa). Acaulospora sp.06 is the dominant species in all treatments. Neutral soil is optimal condition for growth of AMF and sorghum in all indicators including survival after transplanting (100%), species appearance (4 morphotaxa), spore number increasing (39 times) and root colonization of AMF (53.3%). Then, species diversity index has highest both of Shannon-Wiener (H’=1.32) and Simpson (C=0.72). The results showed that neutral soil affects to species number and the appearance of AMF growth. Trap culture using sorghum is good method to show AMF species in their living environment.